ChemInform Abstract: Photocatalytic Water Oxidation by a Pyrochlore Oxide upon Irradiation with Visible Light: Rhodium Substitution into Yttrium Titanate. Issue 13 (March 2015) - Kiss, Borbala; Didier, Christophe; Johnson, Timothy; Manning, Troy D.; Dyer, Matthew S.; Cowan, Alexander J.; Claridge, John B.; Darwent, James R.; Rosseinsky, Matthew J.
Abstract A stable visible‐light driven photocatalyst (λ ≥ 450 nm) for H2O oxidation is prepared by Rh substitution into the pyrochlore Y2Ti2O7 to a maximum level of 2% by stoichiometric solid state reactions of Y2O3, TiO2, and Rh2O3 under air (Pt foil lined alumina boat, 1300 °C, 2 d).